Respuesta :

Answer: i think the answers D.

Step-by-step explanation:

Answer:

The correct option is 4.

Step-by-step explanation:

According to the Pythagoras theorem, the sum of squares of two legs of a triangle is equal to the square of the hypotenuse of the triangle.

[tex](hypotenuse)^2=(leg_1)^2+(leg_2)^2[/tex]

From the given figure it is clear that the length of one leg is 4 ft and the length of second leg is 7 ft.

Using Pythagoras theorem, we get

[tex](hypotenuse)^2=(4)^2+(7)^2[/tex]

[tex](hypotenuse)^2=16+49[/tex]

[tex](hypotenuse)^2=65[/tex]

Taking square root both the sides.

[tex]hypotenuse=\sqrt{65}[/tex]

The length of the hypotenuse is √(65) ft . Therefore the correct option is 4.